IMPROVING WRITING SKILLS FOR BEGINNING THROUGH FINGER PAINTING CHILD MILD MENTAL RETARDATION - Elisa Putri Utama (Universitas Negeri Padang, 2014)
Abstrack: This research is motivated by problems in children researchers found mild mental retardation X class IV SLB Fan Redha Padang can not write the beginning. This study aims to improve children's writing skills beginning for mild mental retardation. This research is a single research subject (SSR). This study used a design-B. finger painting results showed to be effective in improving writing skills for children beginning at SLB mild mental retardation Fan Redha Padang. Kata kunci: Menulis permulaan, finger painting, anak tunagrahita ringan.